A dry material for tundish with the function of cleaning molten steel

By using magnesium calcium sand and spinel as raw materials, combined with boron anhydride or boric acid as bonding agent, the problems of "hydrogenation" and "carbonization" of molten steel are solved, and the cleanliness and service life of molten steel are improved. Avoid pollution of harmful substances, realize the convenience of construction and energy conservation.

CN116655395BActive Publication Date: 2024-12-31武汉钢铁有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310728392.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-31
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

The existing tundish-type materials will cause "hydrogenation" and "carbonization" of molten steel at high temperatures, and organic bonding agents will carbonize and pollute molten steel, affecting the cleanliness of molten steel, and inorganic bonding agents will be difficult to sinter, which will produce irritating gases. Short life span.

Method used

Magnesium calcium sand and spinel are used as the main raw materials, combined with boron anhydride, boric acid or sodium borate as the binding agent, and then fired under controlled heating conditions through stirring to avoid moisture residues and harmful substances, and enhance the resistance to slag corrosion.

Benefits of technology

Effectively prevent the "hydrogenation" and "carbonization" of molten steel, improve the cleanliness of molten steel, extend the service life, avoid the production of toxic substances, save energy, facilitate construction, and improve economic and social benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a tundish dry material with the function of cleaning molten steel. The composition of the tundish dry material is calculated by mass percentage: 5-15% of magnesia-calcium sand aggregate with a particle size of 5-3mm; 5-15% of magnesia-calcium sand aggregate with a particle size of 3-1mm; 3-7% of magnesia-calcium sand aggregate with a particle size less than 1mm; 15-20% of magnesia-calcium sand powder with a particle size less than 0.075mm; 5-15% of spinel aggregate with a particle size of 5-3mm; 5-15% of spinel aggregate with a particle size of 3-1mm; 3-7% of spinel aggregate with a particle size less than 1mm; 15-20% of spinel powder with a particle size less than 0.075mm; 8-10% of sintering promoter; and 8-10% of binder. The invention can not only avoid the occurrence of "hydrogenation" and "carbon increase" phenomena, but also has the function of cleaning molten steel, and at the same time has the characteristics of strong corrosion resistance, long service life and convenient construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a tundish dry material. Background Art

[0002] With the increasing market demand for clean steel, steelmaking technology is also developing towards cleanliness. As an important part of the continuous casting process, the tundish is the last container for molten steel, which plays a vital role in ensuring the quality and cleanliness of molten steel. The refractory lining of the tundish is in direct contact with the molten steel, so the industry has put forward higher requirements for it, such as purification of molten steel, longevity, and heat preservation.

[0003] The tundish working lining is eroded and washed by high-temperature molten steel and slag, and needs to have good slag erosion resistance and penetration ability, high strength, low thermal conductivity, and the ability to purify molten steel. As the fourth-generation tundish working lining material, the tundish dry material has the advantages of not needing to add any liquid, convenient construction by vibration molding, short baking time and energy saving, and has therefore been rapidly developed and applied.

[0004] At present, the dry materials of the tundish mainly use magnesium and calcium raw materials, and the binders are mostly resins, asphalt, and other organic substances. Studies have shown that magnesium and magnesium-calcium raw materials contain a large amount of adsorbed water and crystallized water, and the hydroxyl groups in the minerals can generate water when removed at high temperatures. In addition, calcium raw materials are easy to absorb moisture and hydrate in a cold state, which will leave residual water in the lining, resulting in the phenomenon of "hydrogenation" of molten steel. The use of organic binders such as resins and asphalt will produce harmful substances such as formaldehyde and free phenol at high temperatures, polluting the environment, and the organic binders will carbonize, causing "carbon increase" in the molten steel. Organic binders harm the environment, pollute molten steel, and are expensive, while inorganic binders such as phosphates, silicates, and sulfates are also difficult to sinter and produce irritating gases. The above factors cause the dry materials of the tundish to cause secondary pollution to the molten steel, affecting the cleanliness of the molten steel. There are difficulties in developing dry materials that can clean the molten steel. Summary of the invention

[0005] The purpose of the present invention is to provide a tundish dry material which can not only avoid the occurrence of "hydrogenation" and "carbonization" phenomena, but also has the function of purifying molten steel, and at the same time has the characteristics of strong corrosion resistance, long service life and convenient construction.

[0006] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0007] A tundish dry material with the function of cleaning molten steel, the composition of which is calculated by mass percentage as follows:

[0008] 5-15% of magnesia-calcium sand aggregate with a particle size of 5-3 mm;

[0009] 5-15% of magnesia-calcium sand aggregate with a particle size of 3-1 mm;

[0010] 3-7% of magnesium calcium sand aggregate with particle size less than 1mm;

[0011] 15-20% magnesium calcium sand powder with a particle size less than 0.075 mm;

[0012] 5-15% spinel aggregate with a particle size of 5-3 mm;

[0013] 5-15% spinel aggregate with a particle size of 3-1 mm;

[0014] 3-7% spinel aggregate with particle size less than 1 mm;

[0015] 15-20% spinel powder with particle size less than 0.075 mm;

[0016] Burning promoter 8-10%;

[0017] Binder 8-10%.

[0018] According to the above scheme, the MgO content in the magnesia-calcium sand aggregate and magnesia-calcium sand powder is ≥70wt%, the CaO content is 20-30wt%, the SiO2 content is ≤0.2wt%, the Fe2O3 content is ≤0.4wt%, the TiO2 content is 0.8-1.2wt%, and the ignition loss content is ≤0.5wt%.

[0019] According to the above scheme, the spinel aggregate and spinel powder are sintered or fused spinel, with Al2O3 content ≥48wt%, MgO content 45-50wt%, CaO content ≤0.6wt%, SiO2 content ≤0.3wt%, Na2O content ≤0.2wt%, and Fe2O3 content ≤0.4wt%.

[0020] According to the above scheme, the sintering agent is one of magnesium calcium iron sand, light clay, iron powder, magnesium powder or any mixture thereof.

[0021] According to the above scheme, the magnesium calcium iron sand has a Mg content of ≥80wt%, a CaO content of 5-10wt%, a Fe2O3 content of 5-8wt%, an Al2O3 content of ≤0.5wt%, and a SiO2 content of ≤1wt%.

[0022] According to the above scheme, the light clay has an Al2O3 content of 30% to 48wt%, a SiO2 content of 50% to 65wt%, and a Fe2O3 content of ≤0.5wt%.

[0023] According to the above scheme, the iron powder has a Fe content of ≥98wt%, a Mn content of ≤0.4wt%, a Si content of ≤0.2wt%, and a C content of ≤0.05wt%.

[0024] According to the above scheme, the magnesium powder has a Mg content of ≥98wt%, a Fe content of ≤0.2wt%, and a H2O content of ≤0.1wt%.

[0025] According to the above scheme, the binder is one of boric anhydride, boric acid, sodium borate or any mixture thereof.

[0026] The method for preparing the above-mentioned tundish dry material with the function of cleaning molten steel comprises the following steps:

[0027] First, the magnesium calcium sand aggregate, magnesium calcium sand powder, spinel aggregate and spinel powder are mixed evenly, and then the sintering promoter and binder are added therein and mixed evenly to obtain the finished product.

[0028] When constructing on site, first pour the dry material into the bottom of the tundish, the material layer thickness reaches the specified requirements, and the surface is flat, then install the mold, pour the dry material into the gap formed by the mold and the cladding, fill it to the upper edge of the tundish, turn on the motor to vibrate for 5 minutes, add more material, repeat the vibration and feeding steps until the dry material fills the rim tightly. Turn on the baking device on the mold, control the heating rate at 6℃ / s, heat to 300℃, and keep it warm for 4 hours. Cool down to below 100℃ and demould.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention uses magnesia calcium sand and spinel as main raw materials, which do not contain crystal water and do not absorb moisture, effectively eliminating the problem of "hydrogenation" of molten steel caused by residual moisture in the working lining of the tundish. At the same time, CaO in magnesia calcium sand has the characteristics of adsorbing impurities and purifying molten steel, and spinel has good slag erosion resistance and penetration ability, good thermal shock stability, high temperature resistance, and improves the service life of dry materials.

[0031] The binder used is one or more of boric anhydride, boric acid, and sodium borate, which eliminates the problems of organic binders producing harmful substances, polluting the environment, and causing "carbon increase" in molten steel after carbonization, which pollutes molten steel. At the same time, it solves the problems of inorganic binders being difficult to sinter, producing irritating gases, and having a short service life.

[0032] The present invention can prevent "hydrogenation" and "carbonization" of molten steel, improve the cleanliness of molten steel, and ensure the quality of steel billets; it has strong corrosion resistance and prolongs the service life; it does not produce toxic and harmful substances and does not pollute the environment; it does not contain water, reduces baking time, saves energy, is convenient to construct, and has a fast turnover; it can create better economic and social benefits. DETAILED DESCRIPTION

[0033] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0034] The specific implementation method provides a tundish dry material with the function of cleaning molten steel, and its composition is calculated by mass percentage:

[0035] 5-15% magnesia-calcium sand aggregate with a particle size of 5-3mm; 5-15% magnesia-calcium sand aggregate with a particle size of 3-1mm; 3-7% magnesia-calcium sand aggregate with a particle size less than 1mm; 15-20% magnesia-calcium sand powder with a particle size less than 0.075mm; 5-15% spinel aggregate with a particle size of 5-3mm; 5-15% spinel aggregate with a particle size of 3-1mm; 3-7% spinel aggregate with a particle size less than 1mm; 15-20% spinel powder with a particle size less than 0.075mm; 8-10% sintering agent; 8-10% binder.

[0036] Specifically, the magnesia-calcium sand aggregate and magnesia-calcium sand powder have MgO content ≥ 70wt%, CaO content 20-30wt%, SiO2 content ≤ 0.2wt%, Fe2O3 content ≤ 0.4wt%, TiO2 content 0.8-1.2wt%, and loss on ignition content ≤ 0.5wt%.

[0037] Specifically, spinel aggregate and spinel powder are used as sintered or fused spinel, with Al2O3 content ≥48wt%, MgO content 45-50wt%, CaO content ≤0.6wt%, SiO2 content ≤0.3wt%, Na2O content ≤0.2wt%, and Fe2O3 content ≤0.4wt%.

[0038] Specifically, the sintering agent used is one of magnesium calcium iron sand, light clay, iron powder, magnesium powder or any mixture thereof.

[0039] Specifically, magnesium calcium iron sand is used with a Mg content of ≥80wt%, a CaO content of 5-10wt%, a Fe2O3 content of 5-8wt%, an Al2O3 content of ≤0.5wt%, and a SiO2 content of ≤1wt%.

[0040] Light clay is used with an Al2O3 content of 30% to 48wt%, a SiO2 content of 50% to 65wt%, and a Fe2O3 content of ≤0.5wt%.

[0041] The iron powder has a Fe content of ≥98wt%, a Mn content of ≤0.4wt%, a Si content of ≤0.2wt%, and a C content of ≤0.05wt%.

[0042] The magnesium powder used has a Mg content of ≥98wt%, a Fe content of ≤0.2wt%, and a H2O content of ≤0.1wt%.

[0043] Specifically, the binder used is one of boric anhydride, boric acid, sodium borate or any mixture thereof.

[0044] The specific embodiment also provides a method for preparing the above-mentioned tundish dry material with the function of cleaning molten steel:

[0045] First, the magnesium calcium sand aggregate, magnesium calcium sand powder, spinel aggregate and spinel powder are stirred and mixed, and then the sintering promoter and binder are added and stirred and mixed to obtain the finished product.

[0046] Example 1

[0047] A tundish dry material with the function of cleaning molten steel, the composition of which is calculated by mass percentage:

[0048] 10% magnesia-calcium sand aggregate with a particle size of 5-3mm; 10% magnesia-calcium sand aggregate with a particle size of 3-1mm; 5% magnesia-calcium sand aggregate with a particle size less than 1mm; 15% magnesia-calcium sand powder with a particle size less than 0.075mm; 10% fused spinel aggregate with a particle size of 5-3mm; 10% fused spinel aggregate with a particle size of 3-1mm; 5% fused spinel aggregate with a particle size less than 1mm; 15% spinel powder with a particle size less than 0.075mm; 10% sintering agent (magnesia-calcium iron sand and light clay mixed in a ratio of 1:1); 10% boric acid as a binder.

[0049] First, weigh the magnesia-calcium sand aggregate, magnesia-calcium sand powder, spinel aggregate, and spinel powder in proportion, pour them into a forced mixer and mix for 15 minutes, then weigh the burning promoter and binder in proportion, pour them into the forced mixer and mix for 15 minutes, and the finished product is obtained after stirring evenly.

[0050] When constructing on site, first pour the dry material into the bottom of the tundish, the material layer thickness reaches the specified requirements, and the surface is flat, then install the mold, pour the dry material into the gap formed by the mold and the cladding, fill it to the upper edge of the tundish, turn on the motor to vibrate for 5 minutes, add more material, repeat the vibration and feeding steps until the dry material fills the edge of the cladding tightly. Turn on the baking device on the mold, control the heating rate to 6℃66, heat to 300℃, and keep warm for 4 hours. When the temperature of the dry material drops below 100℃, demould.

[0051] Example 2

[0052] A tundish dry material with the function of cleaning molten steel, the composition of which is calculated by mass percentage:

[0053] 15% magnesia-calcium sand aggregate with a particle size of 5-3mm; 15% magnesia-calcium sand aggregate with a particle size of 3-1mm; 5% magnesia-calcium sand aggregate with a particle size less than 1mm; 15% magnesia-calcium sand powder with a particle size less than 0.075mm; 5% fused spinel aggregate with a particle size of 5-3mm; 5% fused spinel aggregate with a particle size of 3-1mm; 5% fused spinel aggregate with a particle size less than 1mm; 15% spinel powder with a particle size less than 0.075mm; 10% sintering agent (a mixture of light clay and iron powder in a ratio of 1:1); 10% boric anhydride as a binder.

[0054] First, weigh the magnesia-calcium sand aggregate, magnesia-calcium sand powder, spinel aggregate, and spinel powder in proportion, pour them into a forced mixer and mix for 15 minutes, then weigh the burning promoter and binder in proportion, pour them into the forced mixer and mix for 15 minutes, and the finished product is obtained after stirring evenly.

[0055] When constructing on site, first pour the dry material into the bottom of the tundish, the material layer thickness reaches the specified requirements, and the surface is flat, then install the mold, pour the dry material into the gap formed by the mold and the cladding, fill it to the upper edge of the tundish, turn on the motor to vibrate for 5 minutes, add more material, repeat the vibration and feeding steps until the dry material fills the edge of the cladding tightly. Turn on the baking device on the mold, control the heating rate to 6℃66, heat to 300℃, and keep warm for 4 hours. When the temperature of the dry material drops below 100℃, demould.

[0056] Example 3

[0057] A tundish dry material with the function of cleaning molten steel, the composition of which is calculated by mass percentage:

[0058] 5% magnesia-calcium sand aggregate with a particle size of 5-3mm; 5% magnesia-calcium sand aggregate with a particle size of 3-1mm; 7% magnesia-calcium sand aggregate with a particle size less than 1mm; 15% magnesia-calcium sand powder with a particle size less than 0.075mm; 15% sintered spinel aggregate with a particle size of 5-3mm; 15% sintered spinel aggregate with a particle size of 3-1mm; 3% sintered spinel aggregate with a particle size less than 1mm; 15% spinel powder with a particle size less than 0.075mm; 10% sintering promoter (a mixture of light clay and magnesium powder in a ratio of 1:1); 10% binder (a mixture of boric acid and sodium borate in a ratio of 1:1).

[0059] First, weigh the magnesia-calcium sand aggregate, magnesia-calcium sand powder, spinel aggregate, and spinel powder in proportion, pour them into a forced mixer and mix for 15 minutes, then weigh the burning promoter and binder in proportion, pour them into the forced mixer and mix for 15 minutes, and the finished product is obtained after stirring evenly.

[0060] When constructing on site, first pour the dry material into the bottom of the tundish, the material layer thickness reaches the specified requirements, and the surface is flat, then install the mold, pour the dry material into the gap formed by the mold and the cladding, fill it to the upper edge of the tundish, turn on the motor to vibrate for 5 minutes, add more material, repeat the vibration and feeding steps until the dry material fills the edge of the cladding tightly. Turn on the baking device on the mold, control the heating rate to 6℃66, heat to 300℃, and keep warm for 4 hours. When the temperature of the dry material drops below 100℃, demould.

[0061] The common dry material is used as a control group for comparison: 25wt% magnesia aggregate with a particle size of 5-3mm; 25wt% magnesia aggregate with a particle size of 3-1mm; 20wt% magnesia aggregate with a particle size less than 1mm; 24wt% magnesia powder with a particle size less than 0.075mm; 5wt% resin; 1wt% silicate. The practice of the steel plant proves that the tundish using the dry material of the present invention has significantly improved the hydrogen increase amount, carbon increase amount, and inclusion qualified rate of the performance molten steel compared with the ordinary dry material, and the service life is greatly improved. The specific data are shown in the table below.

[0062] Example 1 Example 2 Example 3 Ordinary dry material Hydrogenation amount (ppm) 0.5 0.6 0.4 0.8 Carbon addition (%) 0.01 0.00 0.01 0.03 Inclusion qualification rate (%) 98.97 98.32 98.85 94.51 Service life (furnace) 21 26 22 17 .

Claims

1. A tundish dry material with the function of cleaning molten steel, characterized in that The composition is calculated by mass percentage as follows: 5~15% of magnesia-calcium sand aggregate with a particle size of 5~3mm; 5~15% of magnesia-calcium sand aggregate with a particle size of 3~1mm; 3~7% of magnesium calcium sand aggregate with particle size less than 1mm; 15-20% magnesium calcium sand powder with particle size less than 0.075mm; Spinel aggregate with a particle size of 5 to 3 mm: 5 to 15%; Spinel aggregate with a particle size of 3 to 1 mm: 5 to 15%; Spinel aggregate with particle size less than 1 mm 3~7%; Spinel powder with particle size less than 0.075 mm 15-20%; Burning promoter 8~10%; binder 8~10%; The sintering agent is one of magnesium calcium iron sand, light clay, iron powder, magnesium powder or any mixture thereof; The binder is one of boric anhydride, boric acid, sodium borate or any mixture thereof; The magnesia-calcium sand aggregate and magnesia-calcium sand powder contain MgO content ≥ 70wt%, CaO content 20-30wt%, SiO2 content ≤ 0.2wt%, Fe2O3 content ≤ 0.4wt%, TiO2 content 0.8-1.2wt%, and loss on ignition content ≤ 0.5wt%; The spinel aggregate and spinel powder are sintered or fused spinel, with Al2O3 content ≥48wt%, MgO content 45-50wt%, CaO content ≤0.6wt%, SiO2 content ≤0.3wt%, Na2O content ≤0.2wt%, and Fe2O3 content ≤0.4wt%.

2. The tundish dry material with the function of cleaning molten steel as claimed in claim 1, characterized in that The magnesium calcium iron sand has a Mg content of ≥80wt%, a CaO content of 5-10wt%, a Fe2O3 content of 5-8wt%, an Al2O3 content of ≤0.5wt%, and a SiO2 content of ≤1wt%.

3. The tundish dry material with the function of cleaning molten steel as claimed in claim 1, characterized in that The light clay has an Al2O3 content of 30% to 48wt%, a SiO2 content of 50% to 65wt%, and a Fe2O3 content of ≤0.5wt%.

4. The tundish dry material with the function of cleaning molten steel as claimed in claim 1, characterized in that The iron powder has a Fe content of ≥98wt%, a Mn content of ≤0.4wt%, a Si content of ≤0.2wt%, and a C content of ≤0.05wt%.

5. The tundish dry material with the function of cleaning molten steel as claimed in claim 1, characterized in that The magnesium powder has a Mg content of ≥98wt%, a Fe content of ≤0.2wt%, and a H2O content of ≤0.1wt%.